Guidelines for electrical transmission line structural loading - Miller, Michael D.; Wong, C. Jerry (ASCE manuals and reports on engineering practice ;, 2010)
The understanding of transmission line structural loads continues to improve as a result of research, testing, and field experience. Guidelines for Electrical Transmission Line Structural Loading, Third Edition provides the most relevant and up-to-date information related to structural line loading. Updated and revised, this edition covers weather-related loads, relative reliability-based design, and loading specifics applied to prevent cascading types of failures, as well as loads to protect against damage and injury during construction and maintenance. This manual is intended to be a resource that can be readily absorbed into a loading policy. It will be valuable to engineers involved in utility, electrical, and structural engineering.